Synthesis and Characterization of Some Novel Alkyl-2n-butyl- - kaur, rupinder (International Journal of Pharmaceutical & Biological Archive, 2010)
In the present studies, a series of Alkyl-2-n-butyl-1-[4’(2’’- Carboxyphenyl-1’’-yl) benzyl] benzimidazole-5-sulphonates were prepared. 2-Butyl benzimidazole was coupled with 4-Chloromethylbiphenyl-2’-carboxylic acid to form 2-Butyl-1- [(2’-carboxybiphenyl-4-yl) methyl] benzimidazole which on treatment with chlorosulphonic acid yield 2-n-Butyl-1-[4′ (2′′-carboxybiphenyl-4-yl) methyl] benzimidazole-5-sulphonyl chloride. The latter on reaction with various aliphatic alcohols yield corresponding sulphonate derivatives. All the synthesized compounds were identified by IR, 1H-NMR and MS.